Analysis of Nite Sky Brightness on Star Observation in the City of Makassar - Baso Surya Al-Qadri; Rahma Amir; Andi Syam Rizal (Astroislamica: Journal of Islamic Astronomy, 2026)
This The main research problem of this study is how the brightness of the night sky affects the visibility of stars in Makassar City, and what solutions can be applied to overcome the limitations caused by light pollution. This problem is formulated into two sub-problems: (1) How does night sky brightness impact stellar observation in Makassar? and (2) What strategies can be used to address the challenges of observing under urban sky conditions? This study employs a descriptive mixed-method approach with a falak-astronomical perspective. Quantitative data were obtained from secondary measurements of night sky brightness using Light Pollution Map values expressed in mag/arcsec² and classified through the Bortle Scale. Qualitative analysis was conducted by interpreting the observational implications of skyglow on falak practices and stellar visibility. Data were collected from four observation locations: Pantai Losari, Pantai Tanjung Layar Putih, UIN Samata, and Malino.The results show significant variation in sky brightness across the locations. Pantai Losari recorded the lowest darkness level (18.85 mag/arcsec²), categorized as urban sky, where only bright stars can be observed. Meanwhile, Malino showed the darkest condition (21.01 mag/arcsec²), classified as rural sky, allowing clearer visibility of faint stars. These findings confirm that increasing urban light pollution reduces the limiting magnitude and restricts astronomical observation in falak studies. The implications of this research are: (1) night sky brightness is a crucial factor in supporting observational astronomy; (2) the study highlights the need for darker observation zones around Makassar; and (3) it strengthens the relevance of integrating falak tradition with modern sky-quality analysis to preserve accurate celestial observation.